In Situ-forming Collagen Hydrogels Crosslinked by Multifunctional Polyethylene Glycol as a Matrix Therapy for Corneal Defects: 2-Month Follow-up In Vivo. Issue 1 (10th January 2023) - Logan, Caitlin M.; Fernandes-Cunha, Gabriella Maria; Chen, Fang; Le, Peter; Mundy, David; Na, Kyung Sun; Myung, David
Abstract : Purpose: We recently showed that in situ-forming collagen gels crosslinked through multifunctional polyethylene glycol (PEG) supported corneal epithelialization 7 days after treatment of lamellar keratectomy wounds. In this study, we aimed to evaluate the longer-term regenerative effects of this gel in animals. Method: Corneal wound healing was assessed 60 days after lamellar keratectomy and gel treatment using slitlamp examination, optical coherence tomography (OCT), pachymetry, corneal topography, an ocular response analyzer, and tonometry. The corneas were evaluated for the presence of beta-tubulin, cytokeratin 3, zonula occludens-1, and alpha smooth muscle actin (SMA) markers. Gene expression of aldehyde dehydrogenase 3A1 (ALDH3A1), cluster of differentiation 31, CD163, alpha-SMA, hepatocyte growth factor, and fibroblast growth factor 2 (FGF-2) and protein expression of CD44 and collagen VI were evaluated. Results: Intraocular pressure, corneal thickness, and hysteresis for the corneas treated with collagen–PEG gels did not significantly change compared with the saline group. However, placido disk topography revealed greater regularity of the central cornea in the gel-treated group compared to the saline group. The gel-treated group exhibited a lower degree of epithelial hyperplasia than the saline group. Immunohistochemical and gene expression analysis showed that the gel-treated corneas exhibited lower alpha-SMA expression compared with the saline group. CD163 and CD44 were found to be elevated in the saline-treated group compared with normal corneas. Conclusions: The in situ-forming collagen-PEG gel promoted epithelialization that improved central corneal topography, epithelial layer morphology, and reduced expression of fibrotic and inflammatory biomarkers after 60 days compared to the saline group.